Measuring VaR of Discounted Cash Flows. Application to a Business Case (2019)
This article seeks to appropriate a Cash Flow at Risk –CFAR- model from the literature developed in the research of Postgraduate, Measuring Value at Risk of Discounted Cash Flow for the Colombian Firm not listed on the stock market and apply it to a non-financial firm at the real sector, which specifies the operational and macroeconomic variables as random results, in a process of statistical modeling by Monte Carlo simulation approach structured in order to measure the variation in future cash flows discounted by a risk-adjusted rates for applications such as toolmaking decisions through the CFaR.